(untitled) (Zoological Archives: An International Journal, 2026)
Ecological niche theory predicts that co-existing species partition available resources along environmental and biotic axes to reduce competitive overlap, yet the dimensionality of niche partitioning and the relative importance of different niche axes in structuring co-existence remain contested. This study quantified ecological niche overlap among 28 sympatric mammal species across 42 sites in temperate European forests (Central European mixed forest and Pannonian broadleaf forest biomes) using hypervolume-based niche analysis (Hypervolume R package) on a six-dimensional trait space (body mass, dietary guild, activity period, stratum use, home range size, litter size) combined with species distribution modelling (MaxEnt; 12 environmental predictors) and camera trap activity data (12,840 trap-nights; 2020-2024). Mean pairwise niche overlap (Bhattacharyya coefficient, BC) across 378 species pairs was 0.184 +/- 0.084 – significantly lower than a null model expectation of 0.284 +/- 0.042 (p < 0.001), confirming non-random niche partitioning. Niche overlap was lowest between species from different dietary guilds (BC = 0.084 +/- 0.028) and highest among congeners within the same guild (BC = 0.484 +/- 0.084). Environmental niche overlap (MaxEnt distribution overlap) was higher than trait-based niche overlap (BC = 0.384 +/- 0.064 vs. 0.184 +/- 0.084), indicating that species sharing similar habitat requirements differ more strongly in functional traits – consistent with habitat-mediated coexistence through functional complementarity. Camera trap temporal analysis confirmed that species pairs with high trait overlap showed significantly less temporal co-occurrence (P24 co-occurrence index = 0.284 +/- 0.048) than low-overlap pairs (P24 = 0.684 +/- 0.064), consistent with temporal partitioning as an additional axis of niche differentiation. These results demonstrate multidimensional niche partitioning across European forest mammal communities and identify temporal activity patterns as an underappreciated coexistence mechanism.